Rainfall Based Dynamic Flood Inundation Simulation for Kelani River Basin of Sri Lanka - Piratheeparajah, N. (Geology, 2023)
Kelani river basin is inundated annually, primarily by heavy precipitation and rapid unplanned development, causing physical, social, and economic impacts. Two major attribut able factors are inefficient rainfall forecasting and flood inundation modeling to facilitate flood management in this region. This study aims to simulate flood inundation in the Kelani River Basin in Sri Lanka using the Hydrological Engineering Center – River Analysis System (HEC-RAS). The model was used to create the scenarios for the elevation of the Kelani River basin, river network, water levels of the five hydrometric stations in the upper stream, land use and the land cover of the river basin were produced to identify the flood inundation and to suggest the possible solutions. A digital terrain model of the river basin was developed from elevation data using GIS techniques. HEC-RAS is the suitable analysis system to identify the flood inundation area by the receiving rainfall on every scale of the rain gauge, and the received rainfall can make the prediction earlier. According to the models of HEC-RAS on terrain, rainfall, river network, and water level of this study, following areas such as Kolonnawa, Hanwella, Homagama, and Kaduwela areas were inundated in the Colombo district after receiving above 85mm rainfall in the catchment areas of Kelani river basin and Wattala, Kelani, Biyagama, Ja-Ela in Gampaha district inundated after receiving 110 mm. It is proposed to build a reservoir in the Glanhouse area, along with a water retention bund in Hanwella, Dompe, Kolonnawa, Biyagama, and Kelani, to protect the vulnerable areas from frequent floods
Keywords: Kelani River basin; Inundation; Dynamic modeling; Rainfall prediction